Rational modulation of the innate immune system for neuroprotection in ischemic stroke - Amantea, Diana; Micieli, Giuseppe; Tassorelli, Cristina; Cuartero, María I.; Ballesteros, Iván; Certo, Michelangelo; Moro, María A.; Lizasoain, Ignacio; Bagetta, Giacinto (Frontiers in Neuroscience, 2015)
The innate immune system plays a dualistic role in the evolution of ischemic brain damage and has also been implicated in ischemic tolerance produced by different conditioning stimuli. Early after ischemia, perivascular astrocytes release cytokines and activate metalloproteases (MMPs) that contribute to blood–brain barrier (BBB) disruption and vasogenic oedema; whereas at later stages, they provide extracellular glutamate uptake, BBB regeneration and neurotrophic factors release. Similarly, early activation of microglia contributes to ischemic brain injury via the production of inflammatory cytokines, including tumor necrosis factor (TNF) and interleukin (IL)-1, reactive oxygen and nitrogen species and proteases. Nevertheless, microglia also contributes to the resolution of inflammation, by releasing IL-10 and tumor growth factor (TGF)-beta, and to the late reparative processes by phagocytic activity and growth factors production. Indeed, after ischemia, microglia/macrophages differentiate towards several phenotypes: the M1 pro-inflammatory phenotype is classically activated via toll-like receptors or interferon-γ, whereas M2 phenotypes are alternatively activated by regulatory mediators, such as ILs 4, 10, 13 or TGF-beta. Thus, immune cells exert a dualistic role on the evolution of ischemic brain damage, since the classic phenotypes promote injury, whereas alternatively activated M2 macrophages or N2 neutrophils prompt tissue remodeling and repair. Moreover, a subdued activation of the immune system has been involved in ischemic tolerance, since different preconditioning stimuli act via modulation of inflammatory mediators, including toll-like receptors and cytokine signaling pathways. This further underscores that the immuno-modulatory approach for the treatment of ischemic stroke should be aimed at blocking the detrimental effects, while promoting the beneficial responses of the immune reaction.